Performance Evaluation of Parallel Concatenated Chaos Coded Modulations - Francisco J. Escribano; Luis Lopez; Miguel A. F. Sanjuan (Journal of Communications Software and Systems, 2008)
In this article we study the performance of a class of parallel concatenated encoders similar to a turbo trellis coded modulation, but where the constituent encoders are chaos coded modulators. We show that, even when the uniform error property does not hold for the kind of constituent chaos coded modulations employed, it is still possible to draw a reasonable bound for the bit error probability at the error floor region based on the interleaver structure. The simulations validate the bounds and show that the dynamics of the underlying chaotic maps, rather than the quantization level of the constituent encoders, is the most important factor to account for both the bit andframe error rate behavior at the error floor region. We alsoshow that these chaos bases parallel concatenated schemes yield performances comparable to binary turbocodes and are thus of potential interest in communications.